‘Doing adoptive family’ in contemporary India – A qualitative exploration of adoptive parents’ narratives - Puhan, Sushri Sangita (Adoption & fostering, 2025)
This article discusses adoptive family practices in India, where biological connections are often seen as more important than social ties and legal recognition in building family relationships. It shares insights from a unique, in-depth study of 11 adoptive parents, connecting their experiences to the concept of ‘family practices’. The article highlights two main points. First, it shows that adoptive families vary in how they create their family lives, especially in response to everyday challenges. These families seek to socially legitimise their understanding of kinship. Second, a continuous process of negotiation and renegotiation is required to create and redefine relationships to demonstrate their familial relationships. While the small group of families studied does not represent all adoptive families in India, the findings reveal the complexities of adoptive family life in a contemporary context. This study provides a strong springboard for further research and can improve social work policy and practice. Plain language summary This article talks about how adoptive families in India navigate their relationships. In the Indian context, biological connections are often seen as more important than social ties and legal recognition when it comes to being a family. This article is based on an in-depth study of 11 adoptive parents, and it explores their everyday experiences and challenges. The article highlights two main ideas. First, it points out that each adoptive family has its own unique way of building their family life, especially when facing everyday challenges. These families work hard to make their relationships feel legitimate and accepted by society. Second, they are constantly negotiating and redefining their connections to prove their familial bonds to others. While this study only includes a small group of families and does not represent every adoptive family in India, it sheds light on the complex realities of adoptive family life today. These insights can pave the way for more research and help improve social work policies and practices.